An Analysis of Special Education Practitioner Journals: A Focus on Behavior. Issue 5 (19th October 2020) - Hott, Brittany L.; Berkeley, Sheri; Reid, Campbell C.; Raymond, Lesli
ABSTRACT: Practitioner journals are one means of translating research to practice. This study explored the extent behavioral interventions for students with mild disabilities are disseminated through special education practitioner journals. Researchers reviewed 3, 298 articles published between 1988 and 2017 in four prominent special education practitioner journals: Beyond Behavior, Intervention in School and Clinic, Teaching Exceptional Children, and Teaching Exceptional Children-Plus . Results suggest that the majority of practitioner articles feature behavior interventions designed to prevent behavior problems from occurring in schools, but relatively few articles shared strategies for managing behaviors as they are occurring or providing consequences after a behavior. Implications for practice and future research inquiry are reported.